Paediatric urolithiasis in emerging economies. (December 2016) - Rizvi, S. Adibul Hasan; Sultan, Sajid; Zafar, Mirza Naqi; Ahmed, Bashir; Aba Umer, Sadaf; Naqvi, S.A. Anwar
Abstract: Background: Paediatric urolithiasis remains endemic in low resource countries. This review highlights the epidemiology, causation and management of urolithiasis in an Asian country in the context of emerging economies. Methods: A literature review of recent articles with key words paediatric urolithiasis, developing countries, endemic stone disease, stone composition, metabolic risk factors, management of paediatric urolithiasis was undertaken and 51 relevant articles were selected with the main focus on experience of this center in managing stone disease in the last two decades. Results: Prevalence of paediatric urolithiasis is high upto 15% affecting children under 15 years with male predominance. Bladder stones still constitutes 10–70% of the burden. Etiology remains unknown where 55% are considered idiopathic, 25% metabolic, 7% infection and 12% due to anatomical abnormalities. Hot climate, poor nutrition, diarrheal diseases are the major causative factors. Chemical composition of stones showed CaOX in 30–63%, AAU in 17–55%, struvite in 8–9%, uric acid in 3–6% and cystine in 1%. Important metabolic risk factors are hypocitraturia in 63–87%, hyperoxaluria in 40–43%, hypocalciuria in 20%, hyperuricosuria in 27%, hyperammonuria in 11–51% and hypovolemia in 31%. Minimally invasive surgery is the mainstay of surgical management. ESWL provides excellent free rates of 84% for smaller stones. PCNL is the option for majority of renal stones with success rates of 89% for simple and 71.5% for complex stones. For bladder stones PUCL and PCCL success rates were 100%. URS for ureteric stones showed clearance rate of 90%. Open surgery is required in 12% of patients with large stone burden. Conclusion: Paediatric urolithiasis remains a devastating health problem in low resource settings. MIS offers relief to majority of patients with excellent stone free rates and short hospital stay. Preventable strategies have to be put in place by improving nutrition and eliminating risk factors by diet and medical intervention. Highlights: Paediatric stone disease remains endemic in emerging economies. Hot climate, poor nutrition and diarrheal disease are the main causative factors. Ammonium hydrogen urate and calcium oxalate stones remain highly prevalent. Hypocitraturia is a major risk factor. MIS is now the mainstay of management of paediatric urolithiasis.